2017
DOI: 10.1016/j.jdeveco.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The fish is the friend of matriliny: Reef density and matrilineal inheritance

Abstract: This paper studies the influence of marine ecology on social institutions of inheritance and descent. In a sample of 79 small-scale horticultural fishing communities in the Solomon Islands, and in samples of 186 to 1,267 societies across the world, we find that coral reef density systematically predicts the prevalence of matrilineal inheritance. Moreover, this result likely reflects adaptation of institutions to ecological conditions, as it holds within ethno-linguistic groups. Reef density explains as much as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
0
22
0
1
Order By: Relevance
“…However, we found fewer significant results with the Austronesian tree, with matrilineal descent correlated with matrilineal inheritance of property, residence and political succession but no economic-or subsistencerelated cultural traits. This result warrants further investigation in the context of hypotheses that are tailored to this region; for example, the 'fish is the friend of matriliny' hypothesis hinges not just on the existence of fishing in a population but also on reef density [19], which might correspond to the relative effort investment required to catch fish. This nuanced view of fishing is not captured in the Ethnographic Atlas, demonstrating a limitation of this type of large-scale comparative analysis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, we found fewer significant results with the Austronesian tree, with matrilineal descent correlated with matrilineal inheritance of property, residence and political succession but no economic-or subsistencerelated cultural traits. This result warrants further investigation in the context of hypotheses that are tailored to this region; for example, the 'fish is the friend of matriliny' hypothesis hinges not just on the existence of fishing in a population but also on reef density [19], which might correspond to the relative effort investment required to catch fish. This nuanced view of fishing is not captured in the Ethnographic Atlas, demonstrating a limitation of this type of large-scale comparative analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Although matriliny is relatively rare across human populations, matrilineal populations are distributed around the world (figure 1). Previous studies of matriliny have often focused on one geographical region or a single language family, and relatively few analyses have accounted for phylogenetic relationships between studied populations [14,19]. In a key phylogenetically controlled study, Holden and Mace assembled data on rules of descent (binarized as 'matriliny' versus 'patriliny') and on the presence or absence of cattle across 68 Bantu-and Bantoid-speaking populations [14].…”
Section: Introductionmentioning
confidence: 99%
“…That said, direct positive outcomes associated with female-biased kinship institutions are not inevitable. A recent comparison of societies with matrilineal and patrilineal inheritance within both the Solomon Islands and the global Standard Cross-Cultural Sample finds very little evidence that matrilineal inheritance translates into real economic or political power in either sample [110]. In short, this body of literature, together with the results of the study reported here, suggests that a more careful understanding of the links between normative patterns (or institutions) and social outcomes is needed.…”
Section: (C) Implications For Female-biased Kinshipmentioning
confidence: 57%
“…Munculnya sistem kekerabatan tertentu dipengaruhi oleh adaptasi masyarakat terhadap lingkungan ekologi dan keputusan investasi yang terbaik (BenYishay, Grosjean, & Vecci, 2017). Sistem matrilineal biasanya diterapkan pada masyarakat agraris yang sumber ekonomi utamanya adalah pertanian holtikultura yang dapat dikerjakan oleh tenaga kerja perempuan dan tidak terlalu mengandalkan tenaga laki-laki.…”
Section: Sistem Kekerabatan Matrilineal DI Suku Minangunclassified